Genetic spectrum of Charcot–Marie–Tooth disease associated with myelin protein zero gene variants in Japan. Issue 3 (27th November 2020) - Taniguchi, Takaki; Ando, Masahiro; Okamoto, Yuji; Yoshimura, Akiko; Higuchi, Yujiro; Hashiguchi, Akihiro; Shiga, Kensuke; Hayashida, Arisa; Hatano, Taku; Ishiura, Hiroyuki; Mitsui, Jun; Hattori, Nobutaka; et al.
Abstract: We aimed to reveal the genetic features associated with MPZ variants in Japan. From April 2007 to August 2017, 64 patients with 23 reported MPZ variants and 21 patients with 17 novel MPZ variants were investigated retrospectively. Variation in MPZ variants and the pathogenicity of novel variants was examined according to the American College of Medical Genetics standards and guidelines. Age of onset, cranial nerve involvement, serum creatine kinase (CK), and cerebrospinal fluid (CSF) protein were also analyzed. We identified 64 CMT patients with reported MPZ variants. The common variants observed in Japan were different from those observed in other countries. We identified 11 novel pathogenic variants from 13 patients. Six novel MPZ variants in eight patients were classified as likely benign or uncertain significance. Cranial nerve involvement was confirmed in 20 patients. Of 30 patients in whom serum CK levels were evaluated, eight had elevated levels. Most of the patients had age of onset >20 years. In another subset of 30 patients, 18 had elevated CSF protein levels; four of these patients had spinal diseases and two had enlarged nerve root or cauda equina. Our results suggest genetic diversity across patients with MPZ variants. Abstract : Genetic spectrum of MPZ variants was confirmed in this study.